2018
DOI: 10.4236/jmp.2018.95056
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Harmonic Frequency Pattern Organizes Local and Non-Local States by Quantum Entanglement in both EPR-Studies and Life Systems

Abstract: A novel biophysical principle: the GM-model was revealed, describing an algorithm for coherent and non-coherent electromagnetic (EM) frequencies that either sustain or deteriorate life conditions. The particular frequency bands could be mathematically positioned on a Pythagorean scale, based on information distribution according to ratios of 2:3 in 1:2. The particular scale exhibits a core pattern of twelve eigenfrequency functions with adjacent self-similar patterns, according to octave hierarchy. In view of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…This information is considered to be non-local, a feature that in quantum physics is related to the phenomenon of entanglement. We have recently shown that discrete EM frequency pattern precisely fit earlier EPR experimentation in which such EM radiation promotes states of quantum entanglement [51].…”
Section: Steering By Holographic Memory Hypersphere Of the Individualsupporting
confidence: 69%
See 3 more Smart Citations
“…This information is considered to be non-local, a feature that in quantum physics is related to the phenomenon of entanglement. We have recently shown that discrete EM frequency pattern precisely fit earlier EPR experimentation in which such EM radiation promotes states of quantum entanglement [51].…”
Section: Steering By Holographic Memory Hypersphere Of the Individualsupporting
confidence: 69%
“…These take the form of toroidal organized force vectors that even may extend the cellular membrane surface. This process could be enhanced due to GM-like coherent vibrations that, as mentioned above, have been shown to increase the degree of quantum entanglement [51]. Such a process can especially be anticipated in the quantum de-coherence protected channel interior [101].…”
Section: Steering By Holographic Memory Hypersphere Of the Individualmentioning
confidence: 87%
See 2 more Smart Citations
“…In brackets (nr. ): reference to own publications :(1) Geesink and Meijer, 2016;(2) (3) Meijer and Geesink, 2016;(4) Meijer and Geesink, 2018;(5) Meijer and Geesink, 2018;(6) Geesink and Meijer, 2018 a;(7) Geesink and Meijer, 2018b;(8) Geesink and Meijer, 2018 c;(9) Geesink and Meijer, 2019a;(10) Meijer, 2019c. Supporting research of others: *0: Hamblin et al, 2017;*1: Nardechcia et al, 2017;*2: Ferris, 2006;*3: Tang et al, 2018;*4: Chladni, 1980;*5: Adamatzky, 2013/Hashizume, 2012*6: Irikura, 2007;*7: Rezolla et al, 2003;*8: Selvam, 2007.…”
Section: Semi-harmonic Background Fieldmentioning
confidence: 99%